2017
DOI: 10.5539/ies.v10n4p70
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Effectiveness of Combination Therapy (Based on Executive Function and Sensory Integration) Child-Centered on the Symptoms of Attention Deficit/Hyperactivity Disorder (ADHD)

Abstract: The aim of the present study is to examine the effectiveness of combination therapy based on executive function and sensory integration child-centered on ADHD. For this purpose, from among all first, second and third grade primary school students in Shiraz, 40 children were selected. The selected students were randomly assigned in two groups of experimental (n = 20) and control group (n = 20) by random method through internet call from Education site, and by Clinical Interview, implementation of CSI-4 parent f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“… Yochman et al (2004) found that a high percentage of 4- to 6-year-old children with ADHD fell below lower-bound thresholds (scoring lower than 1.5 SDs below the mean score of the control group) for sensory processing deficits, particularly in sensory modulation, as reported by mothers. SI using fine and gross motor activity has been found to be especially effective in reducing hyperactivity and attentional deficit in school-age children when combined with executive functioning therapy ( Salami et al, 2017 ). Physical activity interventions may be a well-tolerated and beneficial treatment for children and adolescents with ADHD.…”
Section: Enriched Environment Studies In Children With Nddsmentioning
confidence: 99%
See 1 more Smart Citation
“… Yochman et al (2004) found that a high percentage of 4- to 6-year-old children with ADHD fell below lower-bound thresholds (scoring lower than 1.5 SDs below the mean score of the control group) for sensory processing deficits, particularly in sensory modulation, as reported by mothers. SI using fine and gross motor activity has been found to be especially effective in reducing hyperactivity and attentional deficit in school-age children when combined with executive functioning therapy ( Salami et al, 2017 ). Physical activity interventions may be a well-tolerated and beneficial treatment for children and adolescents with ADHD.…”
Section: Enriched Environment Studies In Children With Nddsmentioning
confidence: 99%
“…Indeed, increased physical activity may be a key component of environmental enrichment for children with NDDs 1 , although this possibility has not been widely studied in populations outside of ADHD. Benefits of increased activity have been shown without the other aspects of enriched environments in children with ADHD, but at least one study ( Salami et al, 2017 ) suggests that combination therapy may be most beneficial.…”
Section: Enriched Environment Studies In Children With Nddsmentioning
confidence: 99%
“…Salami et al ( 51 ) conducted a multimodal intervention (based on executive function and sensory integration) for children with attention-deficit/hyperactivity disorder for 8 weeks, 3 times/week, 1.5 h/time, the results showed that combination therapy based on executive function and sensory integration child-centered reduces attention deficit and hyperactivity. Valõe et al ( 52 ) studied the long-term effects of multimodal therapy on psychopathology and health-related quality of life in children with ADHD, and the results showed that 36 months of multimodal therapy significantly improved psychopathology and health-related quality of life in children with ADHD, Specifically, the scores of major depressive episode, dysthymic disorder, (hypo) manic episode, attention deficit/hyperactivity disorder, separation anxiety disorder, social phobia, conduct disorder, oppositional defiance disorder, and generalized anxiety disorder were significantly increased.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes the parents of these children may have passive behaviors and treat their children with less warmth. Hence, the vicious cycle between the child's behaviors and parenting strategies continues (10). Numerous epidemiological studies have estimated its prevalence to be 4% to 12% in the school-age population (11).…”
Section: Introductionmentioning
confidence: 99%